Uniqueness of infrared asymptotics in Landau gauge Yang-Mills theory II - Fischer, Christian S.; Pawlowski, Jan M. (Arxiv, 2009)
We present a shortened and simplified version of our proof \cite{Fischer:2006vf} of the uniqueness of the scaling solution for the infrared asymptotics of Green functions in Landau gauge Yang-Mills theory. The simplification relates to a new RG-invariant arrangement of Green functions applicable to general theories. As before the proof relies on the necessary consistency between Dyson-Schwinger equations (DSEs) and functional renormalisation group equations (FRGs). We also demonstrate the existence of a specific scaling solution for both, DSEs and FRGs, that displays uniform and soft kinematic singularities.